Transcribing the second scribe of Beowulf amid obscurity: for <e> and <e> for . (26th April 2019) - Hall, J. R.
Abstract: The second Beowulf scribe often begins the letter with a thick downstroke as for the letter, to which he adds a head and tongue sometimes thinner than the downstroke. On some damaged folios it is debatable whether a certain letter should be read as itself or the remains of in which the head and tongue of are very obscure or simply gone. Further, on fols. 179 and 198v, a later hand, attempting to retrace obscure letters, occasionally restored a letter as that the palaeographic evidence hints was once . At other places the later hand restored a letter as for which there is no evidence for but where is expected. Although the question of for and for is complex, careful study of the comparative evidence, beginning with the eighteenth-century transcripts, A and B, allows us to reach reasonable conclusions.